The Ethics Scandal of Indonesia’s Constitutional Court Chief Justice on Tempo Covers: A Peirce Semiotic Representation Study - Riadi, Ariq Aflah; Maryani, Eni; Dewi, Evie Ariadne Shinta (Faculty of Languages and Arts, Universitas Negeri Padang, 2026)
This study examines how Tempo magazine represents the ethical scandal of the Chief Justice of the Constitutional Court through its October 22 and November 12, 2023 covers. Using a qualitative approach, the study integrates Peirce’s semiotics and Stuart Hall’s theory of representation to analyze how meaning is constructed and ideologically framed in visual media. The findings show that Tempo consistently constructs the scandal not as an isolated personal violation, but as a broader institutional crisis. This representation is produced through the interaction of judicial iconography, metaphors of rupture and collapse, and critical lexical framing. At the micro level, semiotic analysis reveals structured relations among signs that signify weakened judicial legitimacy. At the macro level, these sign patterns function as an encoding strategy that directs audiences toward a preferred reading in which judicial authority is delegitimized and linked to political dynasty. Furthermore, the study demonstrates that Tempo’s visual representation operates as a counter-hegemonic discourse that challenges the normalization of dynastic politics and highlights tensions surrounding judicial independence. By integrating semiotic and representational approaches, this study contributes to a deeper understanding of how media actively constructs political meaning and participates in broader ideological struggles.